2014
DOI: 10.1063/1.4881255
|View full text |Cite
|
Sign up to set email alerts
|

Improved parameterization of interatomic potentials for rare gas dimers with density-based energy decomposition analysis

Abstract: We examine interatomic interactions for rare gas dimers using the density-based energy decomposition analysis (DEDA) in conjunction with computational results from CCSD(T) at the complete basis set (CBS) limit. The unique DEDA capability of separating frozen density interactions from density relaxation contributions is employed to yield clean interaction components, and the results are found to be consistent with the typical physical picture that density relaxations play a very minimal role in rare gas interac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
8
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 107 publications
(77 reference statements)
3
8
0
Order By: Relevance
“…For example, the density-based EDA (DEDA) 66 suggested by Wu et al intuitively would be ideal to guide force field 95,96 , as its frozen density energy is variationally optimized while constraining the total system density to reproduce the sum of the densities of isolated monomers 96 , yielding a more favorable frozen energy and smaller polarization and CT terms than those of the ALMO-EDA. Nevertheless, it was recently revealed that the energy lowering caused by the variational relaxation of the frozen wavefunction is largely due to the so-called "constant-density CT" effect 68 , indicating that a strongly many-body effect is effectively absorbed into the Pauli term.…”
Section: Discussionmentioning
confidence: 99%
“…For example, the density-based EDA (DEDA) 66 suggested by Wu et al intuitively would be ideal to guide force field 95,96 , as its frozen density energy is variationally optimized while constraining the total system density to reproduce the sum of the densities of isolated monomers 96 , yielding a more favorable frozen energy and smaller polarization and CT terms than those of the ALMO-EDA. Nevertheless, it was recently revealed that the energy lowering caused by the variational relaxation of the frozen wavefunction is largely due to the so-called "constant-density CT" effect 68 , indicating that a strongly many-body effect is effectively absorbed into the Pauli term.…”
Section: Discussionmentioning
confidence: 99%
“…Of the available energy decomposition schemes applied to force field development, two of the more well known examples include symmetry-adapted perturbation theory (SAPT) 7,8,[39][40][41][42][43][44][45][46] 5 and variational based EDA approaches. 35,39,[47][48][49][50][51][52] there is no clean separation between polarization and charge transfer in the conventional formulation of SAPT (they both belong to the induction term), although several approaches have been proposed to extract the CT energy. [66][67][68] We shall evaluate AMOEBA using the variational absolutely localized molecular orbital (ALMO)-EDA scheme, 49,52,69 which partitions the total intermolecular interaction energy into contributions of frozen orbital interaction (which contains permanent electrostatics, Pauli repulsion, and dispersion), polarization and CT. New advances made in the ALMO-EDA scheme include (1) the ability to reach a meaningful complete basis set (CBS) limit for polarization and CT using the fragment electric-field response function (FERF) model 70 and…”
mentioning
confidence: 99%
“…The resulting TTSFF could be improved further with the appropriate treatment of the nonbonding interactions in the more crowded systems, but these issues are not related to specifically to transition states. It is well-known that Lennard-Jones potential overestimates the energy in the repulsive region of the van der Waals interaction, and softer potentials (such as Buckingham or buffered 14–7) describe the Pauli repulsion more accurately. , Suffritti collected the existing approaches in his recent article how to get partial charges using experimental data or ab initio electrostatic potentials …”
Section: Resultsmentioning
confidence: 99%